Seven Strains of Enterovirus D68 Detected in the United States during the 2014 Severe Respiratory Disease Outbreak - Brown, B. A. (Genome Announc, 2014)
Clusters of severe respiratory disease in the United States were reported to the CDC beginning in August 2014. Enterovirus D68 (EV-D68) was identified from 83% (30/36) of initial severe cases. Investigations in August and September found severe EV-D68 cases to be widespread across the United States. We report seven EV-D68 genomes from the outbreak.